2020
DOI: 10.1108/ijcthr-08-2019-0138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of destination attractiveness factors and travel motivations on rural homestay choice: the moderating role of need for uniqueness

Abstract: Purpose Rural homestays have emerged as an interesting option for tourists. This study aims to assess the role of destination attractiveness factors and travel motivations in homestay choice. The moderating role of need for uniqueness towards enhancing these relationships is also examined. Design/methodology/approach A survey of 201 Indian tourists who had visited rural homestays in the Uttarakhand state of India was conducted. Data were analyzed using SPSS and WarpPLS, based on structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 105 publications
1
23
1
1
Order By: Relevance
“…In other words, without any increase in accessibility, the motivation of tourists is still high. The results of this study are not in line with Dey et al (2020), and Correia and Pimpao (2008), who concluded that accessibility has a significant effect on tourist motivation. Jin and Weber (2016) concluded that visitors prefer tourist destinations with good accessibility and attractive recreational environments.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In other words, without any increase in accessibility, the motivation of tourists is still high. The results of this study are not in line with Dey et al (2020), and Correia and Pimpao (2008), who concluded that accessibility has a significant effect on tourist motivation. Jin and Weber (2016) concluded that visitors prefer tourist destinations with good accessibility and attractive recreational environments.…”
Section: Resultscontrasting
confidence: 99%
“…The effect of amenities on tourist motivation shows that amenities have a significant effect on There is a positive and significant influence of the attraction variable on the motivation of tourists in Bumiaji tourism village, indicating that if the value of the uniqueness, beauty, and authenticity of the Bumiaji tourism village is maintained and/or increased, it can increase the motivation of tourists to visit this village. This study has extended the study of Dey et al (2020), Al-Kwifi (2015), and Sudaryanti and Sukriah (2015) who stated that attractive attractions and rural culture have a significant influence on tourist motivation. The results of other studies show that the factors that influence tourists to visit tourist destinations are the friendliness of service providers, the attitudes of local people, local culture, and interesting sights (Hasan et al, 2018).…”
Section: Resultssupporting
confidence: 58%
“…Tourists choose places that they find attractive, and that can fulfil their selfidentification needs (Foroudi et al, 2018). Researchers have stated that attractiveness occurs under several factors and conditions, such as the natural, cultural, and social conditions of the destination (Dey et al, 2020;Kim et al, 2012). For example, Kim et al (2012) studied destination attractiveness and reported it to be a result of natural conditions of the destination, its availability, and the local people's attitudes.…”
Section: Memorable Destination Experience and Tourist-destination Identificationmentioning
confidence: 99%
“…Tinjauan literatur mengenai destination attractive, sudah banyak ditelaah oleh beberapa penelitian terdahulu, namun tinjauan ini masih penting untuk dilakukan karena adanya kesenjangan yang terjadi pada hasil-hasil temuan terdahulu. Ketersediaan alternatice akomodasi (Dey et al, 2020); atraksi wisata, fasilitas penunjang, aksesibilitas dan layanan tambahan (Yacob et al, 2019); kebersihan, daya tarik makanan, fasilitas transportasi, fasilitas akomodasi, daya tarik situs, fasilitas komunikasi, biaya, daya tarik budaya, fasilitas tambahan wisata dan kegiatan wisata (Ul & Chaudhary, 2021); infrastruktur, daya tarik sejarah dan budaya, fasilitas komunikasi dan kesamaan gaya hidup (Islam et al, 2017); daya tarik budaya dan infrastruktur (Nasir et al, 2020); motivasi perjalanan dan kondisi sosial (Dey et al, 2020); biaya dari atraksi (Ariya et al, 2017). Sentanu et al (2021), tujuan wisata dapat dilihat sebagai produk kompleks yang terdiri tidak hanya pada keunggulan sumber daya alam akan tetapi mencakup ketersediaan infrastruktur, suprastruktur, layanan, fitur lokal yang khas, atribut budaya dan beberapa faktor lainnya.…”
Section: Pendahuluanunclassified